Optimization of pocket design to produce a thin shape complex profile - Kathirgamanathan, P.; Neitzert, T. (German Academic Society for Production Engineering, 2009)
In extrusion practice surface quality problems like flow lines with thin and varying thicknesses of com¬plex profiles are experienced. Minimization of temperature variance inside the forming zone and velocity variation across the face of the die are particularly important during the metal flow in order to maintain a good quality finish. Several parameters such as shape, depth of pocket, location of die hole and local bearing lengths can be altered to minimize these effects, but fundamental understanding between these parameters and homogeneity of metal flow are very limited in the literature. This study investigates the influence of above-mentioned parameters on the flow behaviour during extrusion for simple and more complex geometries.
Keywords: Extrusion; Pocket design; Optimization